Ice gliding diatoms establish record-low temperature limits for motility in a eukaryotic cell - Qing Zhang; Hope T. Leng; Hongquan Li; Kevin R. Arrigo; Manu Prakash (Proceedings of the National Academy of Sciences, 2025)
Despite periods of permanent darkness and extensive ice coverage in polar environments, photosynthetic ice diatoms display a remarkable capability of living inside the ice matrix. How these organisms navigate such hostile conditions with limited light and extreme cold remains unknown. Using a custom subzero temperature microscope during an Arctic expedition, we present the finding of motility at record-low temperatures in a Eukaryotic cell. By characterizing the gliding motility of several ice diatom species, collected from ice cores in the Chukchi Sea, we record that they retain motility at temperatures as low as − 15 ° C. Remarkably, ice diatoms can glide on ice substrates, a capability absent in temperate diatoms of the same genus. This unique ability arises from adaptations in extracellular mucilage that allow ice diatoms to adhere to ice, essential for gliding. Even on glass substrates where both cell types retain motility at freezing temperatures, ice diatoms move an order of magnitude faster, with their optimal motility shifting toward colder temperatures. Combining field and laboratory experiments with thermo-hydrodynamic modeling, we reveal adaptive strategies that enable gliding motility in cold environments. These strategies involve increasing internal energy efficiency with minimal changes in heat capacity and activation enthalpy, and reducing external dissipation by minimizing the temperature sensitivity of mucilage viscosity. The finding of diatoms’ ice gliding motility opens new routes for understanding their survival within a harsh ecological niche and their migratory responses to environmental changes. Our work highlights the robust adaptability of ice diatoms in one of Earth’s most extreme settings.